2013
DOI: 10.1519/jsc.0b013e3182890ac3
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Reliability, Criterion-Related Validity, and Minimal Detectable Change of the Illinois Agility Test in Male Team Sport Athletes

Abstract: The purposes of this study were first to assess the reliability and criterion-related validity of the Illinois change of direction (COD) Illinois Agility Test (IAGT) and second to determine whether a relationship with power and speed exists. A total of 105 male team sport athletes participated in this investigation. Repeat measurements in 89 subjects out of the 105 were performed to assess the test-retest reliability and the 95% confidence interval (CI) of the difference in the score between paired observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
117
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(141 citation statements)
references
References 33 publications
15
117
0
9
Order By: Relevance
“…ICCs across the two trials in our study were .96 and .97 for NMAT and Ball-NMAT, respectively. These values were in the same range of relative reliability value indices reported in other agility tests (Haj-Sassi, Dardouri, Haj Yahmed, Gmada, Mahfoudhi, & Gharbi, 2009;Haj Sassi, Dardouri, Gharbi, Chaouachi, Mansour, Rabhi et al, 2011;Hachana, Chaabène, Nabli, Attia, Moualhi, Farhat et al, 2013). Haj-Sassi et al (2009) reported an ICC of .92 to .96 across two modified agility T-test trials in men and women physical education students.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…ICCs across the two trials in our study were .96 and .97 for NMAT and Ball-NMAT, respectively. These values were in the same range of relative reliability value indices reported in other agility tests (Haj-Sassi, Dardouri, Haj Yahmed, Gmada, Mahfoudhi, & Gharbi, 2009;Haj Sassi, Dardouri, Gharbi, Chaouachi, Mansour, Rabhi et al, 2011;Hachana, Chaabène, Nabli, Attia, Moualhi, Farhat et al, 2013). Haj-Sassi et al (2009) reported an ICC of .92 to .96 across two modified agility T-test trials in men and women physical education students.…”
Section: Discussionsupporting
confidence: 74%
“…Haj-Sassi et al (2009) reported an ICC of .92 to .96 across two modified agility T-test trials in men and women physical education students. In the same context, Hachana et al (2013) found an ICC of .96 across two Illinois agility run trials in 89team sports players. It is commonly accepted that an ICC over .9 is considered high for physiological field tests (Vincent, 1995); so, our results demonstrated a high reliability of both NAMT and Ball-NMAT.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Agility performance has predominantly been assessing the Change of Direction (COD) movement action in tests such as pro-agility shuttle [8], 505 change of direction test [9], change of direction speed test [10], Y step test [11] and Illinois test [12], that do not involve the assessment of perception [6] and action to a game specific stimulus. The named COD tests principally assess attacking agility actions which further limits their ecological validity in team sports as performance is depen-…”
Section: Introductionmentioning
confidence: 99%